Parent and implementer attitudes on gender-equal caregiving in theory and practice: perspectives on the impact of a community-led parenting empowerment program in rural Kenya and Zambia - Kenneth Okelo; Silas Onyango; Dawn Murdock; Kaylie Cordingley; Kelvin Munsongo; George Nyamor; Patricia Kitsao-Wekulo (BMC Psychology, 2022)
Abstract Background Fathers are often perceived to be mainly responsible for the provision of the family's economic needs. However, past studies have demonstrated that fathers’ involvement in parenting has great significance for the child’s holistic growth and development. Few studies have investigated fathers’ roles in the nurturing care of young children, particularly responsive care and stimulation, in sub-Saharan Africa. The study reported here was carried out as part of a larger study that sought to evaluate the effectiveness of the Moments That Matter (MTM) program in improving the nurturing care of young children in rural communities in Zambia and Kenya. The MTM program uses a parenting empowerment approach to promote bonding and interactions between caregivers and their children within the home, focusing on responsive care, early learning, and security and safety so that children reach their full developmental potential. Trained volunteers facilitated monthly primary caregiver support and learning groups and ECD home visits. Fathers were encouraged to participate in the home visits and to attend some of the group meetings on specific topics. The study reported in this paper aimed to establish the impact of the parenting empowerment program in promoting more gender-equal attitudes and practices on parenting among fathers (who were not the primary caregivers). Methods Qualitative data were collected at three time points (pre-intervention before the implementation began; mid-intervention after 6 months of implementation; and post-intervention, after 24 months). We conducted focused group discussions with primary caregivers (n = 72) and fathers (n = 24) with children below 3 years. In-depth interviews were conducted with ECD Promoters (n = 43) and faith leaders (= 20). We also conducted key informant interviews with the MTM program implementers (n = 8) and government officials (n = 5) involved in the program implementation. We employed thematic analysis to analyse the qualitative data. Results The findings showed that the MTM program resulted in improved gender-equal parenting attitudes and practices among mothers/other primary caregivers and fathers. Study participants reported that most fathers spent more time playing and interacting with their children and were more involved in household chores due to their participation in the MTM program. Conclusion The study findings provide evidence for policy formulation and a guide for implementation of policies that can influence changes in perceived gender roles in parenting.